Factors Affecting Innovations in Tourism in Georgia: Strengthening Sustainable Development Through Competitive and Policy Measures - GOGOLISHVILI, Tinatin (European Journal of Sustainable Development, 2025)
Innovation plays a crucial role in the Georgian tourism industry, which is striving to compete in the global market. This study, based on in-depth interviews, participant observation, and regression analysis, reveals that while both competition and government support significantly impact the level of innovation, their influence is relatively weak. The paper explores this phenomenon by integrating theoretical insights from Chen’s (2017) pre-/post-innovation competition theory and Carvalho’s (2011) agglomeration theory to explain how fragmented firms and a lack of centralized R&D systems diminish the overall innovation impact. Findings indicate that a key reason for this weakness is the lack of a formalized innovation decision-making process within tourism companies in Georgia. Innovation is not consistently embedded in the corporate culture, and management systems often fail to foster a strong orientation toward innovation. This leads to inefficient decision-making, weak implementation of innovative ideas, and limits the sector’s potential for sustainable development. Thus, while competition and state support are vital external drivers, the internal organizational structure and culture play a more significant and challenging role in driving large-scale innovation. Keywords: Innovation, strength of Competition, state policy, Sustainable development